1989
DOI: 10.1007/bf02387663
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant lymphoma of the rectum

Abstract: A rare case of a primary malignant lymphoma of the rectum in a 7 year old girl is presented. Although rectal polyps in children are usually benign juvenile polyps, a rare possibility of malignancy should be kept in mind. An adequate histological examination is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Primary Burkitt lymphoma of the rectum is extraordinarily rare in children. Only a few cases were reported in the English literature over the last 30-40 years [2][3][4][5][6]. We report a 5-year-old girl with fresh rectal bleeding immediately after defecation and a single rectal polyp.…”
Section: Introductionmentioning
confidence: 88%
“…Primary Burkitt lymphoma of the rectum is extraordinarily rare in children. Only a few cases were reported in the English literature over the last 30-40 years [2][3][4][5][6]. We report a 5-year-old girl with fresh rectal bleeding immediately after defecation and a single rectal polyp.…”
Section: Introductionmentioning
confidence: 88%
“…Colonic cases were not subdivided by location. Hirakata et al (7) reported the apparent second case of a primary malignant lymphoma of the rectum in 1989. The 7‐year‐old girl was treated with chemotherapy alone and was alive, asymptomatic, and free of disease 1.5 years after presentation.…”
Section: Commentmentioning
confidence: 99%